2021
DOI: 10.1177/2333794x21989530
|View full text |Cite
|
Sign up to set email alerts
|

Lower Respiratory Tract Infection Trends in East and South-East Asia: In the Light of Economic and Health Care Development

Abstract: This study explored to what degree economic development and improvement of healthcare are associated with lower respiratory tract infection (LRTI) mortality. A correlation analysis between LRTI mortality and Gross Domestic Product (GDP) per capita, and the Health Access and Quality Index (HAQI), respectively was conducted for 15 countries in East and South-East Asia. The results revealed a dramatic decrease in LRTI mortality in total populations for lower-middle income (LMI) countries but at the same time an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Children who were gathered between 2005 2010, and 2014 had a lower risk of developing ARI symptoms. Confirmed by studied conducted in East and South-East Asian nations [ 41 ]. This decrease in the burden of ARI in these developing regions is the result of both a decline in incidence brought on by socioeconomic development and higher living standards as well as a rise in access and quality of care [ 22 ].…”
Section: Discussionmentioning
confidence: 71%
“…Children who were gathered between 2005 2010, and 2014 had a lower risk of developing ARI symptoms. Confirmed by studied conducted in East and South-East Asian nations [ 41 ]. This decrease in the burden of ARI in these developing regions is the result of both a decline in incidence brought on by socioeconomic development and higher living standards as well as a rise in access and quality of care [ 22 ].…”
Section: Discussionmentioning
confidence: 71%
“…Children who were gathered between 2005 2010, and 2014 had a lower risk of developing ARI symptoms. Confirmed by studied conducted in East and South-East Asian nations [37]. This decrease in the burden of ARI in these developing regions is the result of both a decline in incidence brought on by socioeconomic development and higher living standards as well as a rise in access and quality of care [19].…”
Section: Discussionmentioning
confidence: 91%
“…Previous outbreaks of severe acute respiratory syndrome (SARS), Middle East respiratory syndrome (MERS), and the current COVID-19 pandemic have demonstrated that zoonotic diseases are on the rise ( Skowron et al, 2022 ). Moreover, the incidence and burden of lower respiratory tract infections are predicted to increase in our aging population, which can have detrimental effects on healthcare systems if the situation remains unchanged ( Feddema et al, 2021 ). In 2018, the global financial burden of infectious disease epidemics was estimated to be around US$60 billion annually, and the costs of the ongoing COVID-19 pandemic have been estimated to reach US$16 trillion ( Cutler and Summers, 2020 ; Wellcome, 2021 ).…”
Section: Introductionmentioning
confidence: 99%